2014
DOI: 10.2215/cjn.11761113
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy and Progression of CKD

Abstract: Background and objectives Retinal abnormalities may be associated with changes in the renal vasculature. This study assessed the association between retinopathy and progression of kidney disease in participants of the Chronic Renal Insufficiency Cohort (CRIC) study.Design, setting, participants, & measurements This was a prospective study in which patients with CKD enrolled in CRIC had nonmydriatic fundus photographs of both eyes. All CRIC participants in six clinical sites in which fundus cameras were deploye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 17 publications
3
39
0
Order By: Relevance
“…They concluded presence and severity of DR may not provide any additional prognostic information regarding risk of CKD progression and vice versa which is similar with the current study. 12 Previously same observation was found in different studies. Goldstein et al showed that a decline in renal function was not followed by the same decline in retinopathy.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…They concluded presence and severity of DR may not provide any additional prognostic information regarding risk of CKD progression and vice versa which is similar with the current study. 12 Previously same observation was found in different studies. Goldstein et al showed that a decline in renal function was not followed by the same decline in retinopathy.…”
Section: Resultssupporting
confidence: 70%
“…10 Stratton et al, found that there was a highly significant positive association of HbA1c with incidence and progression of retinopathy in both univariate and multivariate analysis. 12 Wong et al also found similar results. 15 Our study showed that the frequency of retinopathy is more in the age group of >50 years.…”
Section: Resultsmentioning
confidence: 55%
“…In multivariable analyses for both outcomes in the MESA, we hierarchically adjusted for gender, other demographics (age, race/ethnicity), cardiovascular comorbidities (diabetes, systolic blood pressure, and eGFR) and other mineral metabolites (FGF23 and PTH). Given the strong links between diabetes and CKD with retinopathy, 45,46 we conducted an a priori analysis that assessed whether the associations of serum phosphate with retinopathy presence and retinal vessel diameter in the fully adjusted model were modified by diabetes or eGFR by testing the significance of interaction terms. Due to effect modification by diabetes presence on the association of phosphate with prevalent retinopathy, we performed stratified analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on the clinical significance of retinopathy on renal outcome produced a variety of different results; some studies showed no adverse effects [11] and others suggested an increased risk of renal failure [13,14]. In our study, patients with diabetes and DMR were associated with a faster eGFR decline after multivariate adjustment, and the slope of eGFR decline was steeper as the DMR grade worsened.…”
Section: Discussionmentioning
confidence: 46%
“…Several studies have evaluated the association between retinopathy and mortality or renal function decline in CKD patients [11,12], but the differences in clinical significance between DMR and HTNR have not been examined in CKD patients. The present study is the first to evaluate whether there is a different relationship between retinopathy and adverse outcomes in CKD patients with DMR and HTNR.…”
Section: Discussionmentioning
confidence: 99%